Self-defense and “retornantes”. The consequences of post-war return migrations in the Andes on the example of illegal settlement of the suburban areas of Ayacucho - Pietraszczyk-Sękowska, Joanna (Koszty współczesnych kryzysów, 2021)
This paper is a case study with an objective to examine the costs of war displacements and the resulting return migrations to the Peruvian Andes based on the example of scarcely researched illegal settlements (so-called invasions) on the outskirts of towns in the province. The analysis focuses on a complex case of a settlement operation involving retornantes, conducted many years after the war by civil self-defense forces. These considerations are supported by the thesis that – due to the diversity and nonobviousness of the determinants – the migratory behaviors of those affected by the armed conflict account for the amorphism of the phenomenon of returns and may contribute to the perpetuation of local crises which arose during the period of terror. The empirical part of the paper was written based on the results of the research conducted in 2004–2010 and 2015–2019 in Lima as well as in towns and rural areas of the central-southern Peruvian Andes.